2018
DOI: 10.3390/s18113768
|View full text |Cite
|
Sign up to set email alerts
|

End-User Feedback on a Low-Cost Portable Air Quality Sensor System—Are We There Yet?

Abstract: Low-cost sensors are a current trend in citizen science projects that focus on air quality. Until now, devices incorporating such sensors have been tested primarily for their technical capabilities and limitations, whereas their usability and acceptability amongst the public rarely goes beyond proof of concept, leaving user experience (UX) unstudied. The authors argue that UX should be taken into account to make sure that products and services are fit for purpose. Nineteen volunteers tested and evaluated a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…Since most of them are designed for measurement only, they generally lack the features necessary for field-based learning, such as display screens and built-in GPS/data loggers/batteries. Many rely on a smartphone GPS to collect location data and use Bluetooth to connect the devices to smartphone applications to view and store air pollution data (Robinson et al, 2018). Furthermore, these mobile applications often work only on an Android phone or do not work well on low-quality phones, requiring instructors to purchase Android phones of reasonable quality in addition to air-monitoring devices to serve all students, and data are often lost when applications crash (Gaskins, A. J. and J. E. Hart, 2019;Robinson et al, 2018).…”
Section: Geoair: a Low-cost Air-pollution Monitor For Health/medical mentioning
confidence: 99%
See 1 more Smart Citation
“…Since most of them are designed for measurement only, they generally lack the features necessary for field-based learning, such as display screens and built-in GPS/data loggers/batteries. Many rely on a smartphone GPS to collect location data and use Bluetooth to connect the devices to smartphone applications to view and store air pollution data (Robinson et al, 2018). Furthermore, these mobile applications often work only on an Android phone or do not work well on low-quality phones, requiring instructors to purchase Android phones of reasonable quality in addition to air-monitoring devices to serve all students, and data are often lost when applications crash (Gaskins, A. J. and J. E. Hart, 2019;Robinson et al, 2018).…”
Section: Geoair: a Low-cost Air-pollution Monitor For Health/medical mentioning
confidence: 99%
“…Many rely on a smartphone GPS to collect location data and use Bluetooth to connect the devices to smartphone applications to view and store air pollution data (Robinson et al, 2018). Furthermore, these mobile applications often work only on an Android phone or do not work well on low-quality phones, requiring instructors to purchase Android phones of reasonable quality in addition to air-monitoring devices to serve all students, and data are often lost when applications crash (Gaskins, A. J. and J. E. Hart, 2019;Robinson et al, 2018). A smartphone application connected to an air monitor often requires technical experience and/or a steep learning curve, causing students to struggle with unnecessarily complicated technical features, which may hinder students in achieving intended learning objectives.…”
Section: Geoair: a Low-cost Air-pollution Monitor For Health/medical mentioning
confidence: 99%
“…For example, devices that are designed to mainly target the general public tend to be easy to use and visually pleasing, but they do not provide sufficient accuracy for credible data [ 16 ], lack the elements required for scientific research, such as data loggers, and are often suitable for measurement only at a fixed location (e.g., a user’s home). In contrast, devices that are widely used by researchers or scientists are often not ready for citizen science applications due to their poor user-friendliness and technical complexity [ 17 , 18 ]. However, they have been frequently employed in community-based participatory research, despite being designed for researchers, scientists, or those who are technically capable.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, stationary monitoring often has little impact on people’s awareness of or behaviors to improve their surrounding air conditions because it does not fully satisfy participants’ curiosity [ 14 ]. It has been reported that people are more interested in identifying the air quality in their own spaces of daily activity than in the general outdoor areas of their communities [ 18 , 21 ] and thus, are more motivated to change their behaviors to reduce air pollution/exposure when they are informed of the air quality in their immediate surroundings [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study was also partially motivated by the problems understanding the outputs of low-cost sensors in the context of their increased noise and cross sensitivities relative to regulatory-grade instruments [15]. Our own field experience and recent papers from the low-cost air quality instrument community have consistently encountered difficulties understanding and interpreting the outputs of low-cost sensors, especially when communicating results to individuals who may not have a highly technical understanding of the instruments and/or atmospheric chemistry [16,17]. This study attempted to address some of these issues by providing an initial interpretation of the sensor outputs that can be produced in near real-time and are output in a way that a user could understand: the likelihood that a type of source is or is not affecting the measured air quality.…”
Section: Introductionmentioning
confidence: 99%